(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Riyani The Label is a Small and Medium Enterprise (MSME) that is currently undergoing a period of business expansion. In response to the evolving landscape, Riyani The Label is endeavouring to include marketing strategies via the TikTok social media platform in order to enhance its visibility within the broader community. The primary objective of this research is to investigate the utilisation of TikTok social media platform for marketing purposes, specifically in relation to the purchasing interest in UMKM Riyani The Label products. The present study was conducted using a quantitative descriptive methodology. The process of data collection involves the utilisation of both field research and literature review. Field research involves the collection of data by direct observation and the distribution of questionnaires, while library research entails the gathering and analysis of diverse references. This study use simple regression as a quantitative data analysis technique. The findings of this study provide an elucidation of the phenomenon of marketing through social media. Specifically, TikTok is categorised as a potent platform in this regard. Furthermore, the study sheds light on the relationship between social media marketing and the inclination to purchase products or services from micro, small, and medium enterprises (UMKM). The products offered by Riyani The Label are categorised as medium. Furthermore, the utilisation of TikTok as a marketing platform has been shown to exert a noteworthy and favourable impact on the consumer’s inclination to purchase products from UMKM Riyani The Label. The findings of this study suggest that Riyani The Label should enhance its proficiency and expertise in using the social media platform TikTok. Additionally, further research is warranted to assess various aspects. Keywords: Marketing through social media, TikTok, buying interest